Trichodes israelicus, eine neue Buntkäferart aus Palästina (Coleoptera: Cleridae). - Winkler, Josef Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1963)
In the present paper the writer describes the new Glerid Trichodes israelicus n. sp. closely related to the species Trichodes leucopsideus (Olivier). Nomenclatural Acts israelicus Winkler, 1963 (Trichodes), spec. n.